Analysis of educated unemployment in Sulawesi: A study of 6 provinces during the period 2014–2023 - Nane Grasela; Kalvin A. Parinding; Mohamad Ichwan; Sitti Rahmawati; Laendatu Paembonan (Priviet Social Sciences Journal, 2026)
This study examines the effects of Provincial Minimum Wage (UMP), Government Expenditure on Education, and the ICT Development Index (IP-TIK) on educated unemployment across six Sulawesi provinces from 2014 to 2023. Using panel data regression on secondary data sourced from the Central Statistics Agency (BPS), the Fixed Effect Model was selected as the best-fit specification based on the Chow Test and Hausman Test. Simultaneously, all three variables significantly influence educated unemployment, with an F-statistic of 141.8002 and an Adjusted R-squared of 0.9502. Partially, UMP exerts a positive and significant effect at the 10 percent significance level, indicating that minimum wage increases tend to elevate educated unemployment as firms adopt more selective recruitment practices. Government expenditure on education shows a negative and significant effect at the same significance level, suggesting that higher education spending reduces educated unemployment, though its impact remains suboptimal given budget realization consistently below the constitutional 20 percent mandate and the inherently long-term nature of education investment returns. IP-TIK, by contrast, yields no significant effect and carries a positive coefficient, reflecting labor substitution by technology and the absence of a sufficient digital development threshold to trigger structural labor market transformation in the region. These findings underscore the need for regionally calibrated minimum wage policies, improved realization of education budgets, and accelerated ICT infrastructure investment as complementary strategies for reducing educated unemployment in Sulawesi.